Post COVID nocardiosis-an opportunistic enemy - Sesodia, Kulwant; Khosla, Pooja; Taneja, Vinus; Dessai, Rishikesh (International Journal of Research in Medical Sciences, 2023)
Nocardia is an opportunistic infection seen mostly in immunocompromised individuals. It has become an important pathogen especially in these post covid times in which multiple individuals had to go through high dose corticosteroid therapy as part of their severe COVID-19 treatment. We present a 62 years old male with diabetes mellitus and hypertension who had previously been hospitalized for a month for COVID-19 and received high dose corticosteroids for the same. He presented again one month later with symptoms of fever and breathlessness and was worked up extensively for infections in which all his investigations came negative. For suspicion of opportunistic pathogen his HRCT thorax was done which showed consolidation and cavitation in lung along with other infective changes. In view of HRCT thorax findings bronchoscopy was done and bronchoalveolar lavage was sent for examination which grew Nocardia beijingensis on culture. Cotrimoxazole was started for the patient and 3 days after the initiation of therapy he became afebrile and was weaned off of oxygen support gradually over next one month.